2003
DOI: 10.1091/mbc.e02-12-0794
|View full text |Cite
|
Sign up to set email alerts
|

Human PIG-U and Yeast Cdc91p Are the Fifth Subunit of GPI Transamidase That Attaches GPI-Anchors to Proteins

Abstract: Many eukaryotic proteins are anchored to the cell surface via glycosylphosphatidylinositol (GPI), which is posttranslationally attached to the carboxyl-terminus by GPI transamidase. The mammalian GPI transamidase is a complex of at least four subunits, GPI8, GAA1, PIG-S, and PIG-T. Here, we report Chinese hamster ovary cells representing a new complementation group of GPI-anchored protein-deficient mutants, class U. The class U cells accumulated mature and immature GPI and did not have in vitro GPI trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
123
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 28 publications
1
123
0
Order By: Relevance
“…Five essential membrane proteins are involved: Gaa1, Gab1, Gpi8, Gpi16, and Gpi17 (Hamburger et al 1995;Benghezal et al 1996;Fraering et al 2001;Ohishi et al 2000Ohishi et al , 2001Hong et al 2003;Grimme et al 2004). Gpi18 is catalytic because it resembles cysteine proteases and mutation of predicted active site residues eliminates its function (Meyer et al 2000).…”
Section: Gpi Anchoringmentioning
confidence: 99%
“…Five essential membrane proteins are involved: Gaa1, Gab1, Gpi8, Gpi16, and Gpi17 (Hamburger et al 1995;Benghezal et al 1996;Fraering et al 2001;Ohishi et al 2000Ohishi et al , 2001Hong et al 2003;Grimme et al 2004). Gpi18 is catalytic because it resembles cysteine proteases and mutation of predicted active site residues eliminates its function (Meyer et al 2000).…”
Section: Gpi Anchoringmentioning
confidence: 99%
“…4 Other subunits were identified as they co-immunoprecipitated with the GPI8/Gpi8p-GAA1/Gaa1p complex. 5,6 Trypanosomatids such as Trypanosoma brucei, share three subunits with mammalian/yeast GPIT (homologues of GPI8, GAA1 and PIG-T termed TbGPI8, TbGAA1 and bGPI16/PIGT, respectively) but have two novel subunits (TTA1 and TTA2) in lieu of PIG-S and PIG-U. 7 We recently found that phosphatidylinositol glycan class U (PIG-U), the human Gab1 orthologue, located on chromosomal band 20q11, is amplified and overexpressed in bladder cancer cell lines and primary tumors and causes malignant transformation in vitro and in vivo.…”
mentioning
confidence: 99%
“…Proteins destined to be GPI-anchored have a signal sequence at their C termini that directs GPI anchoring: GPI transamidase cleaves the signal sequence and replaces it with preassembled GPI anchor (5). Human and Saccharomyces cerevisiae GPI transamidases are well conserved, containing five homologous components (8). Five human components, GAA1, GPI8, PIG-S, PIG-T, and PIG-U are homologous to yeast Gaa1p, Gpi8p, Gpi17p, Gpi16p, and Cdc91p, respectively (8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Human and Saccharomyces cerevisiae GPI transamidases are well conserved, containing five homologous components (8). Five human components, GAA1, GPI8, PIG-S, PIG-T, and PIG-U are homologous to yeast Gaa1p, Gpi8p, Gpi17p, Gpi16p, and Cdc91p, respectively (8)(9)(10)(11)(12)(13)(14)(15). Several lines of evidence indicate that GPI8 and Gpi8p are catalytic components responsible for cleavage of GPIattachment signal sequences (10,13,(16)(17)(18).…”
mentioning
confidence: 99%